2015
DOI: 10.1016/j.jaridenv.2014.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating the dry forests of South America: Diversity of land users and imprints on ecosystem functioning

Abstract: In the South American dry forest of the Dry Chaco and Chiquitania, the area under cultivation rose from 10% to 19% over the last ten years, and little biophysical, economical, or political constrains seem to prevent further expansion. Although typically associated to a homogeneous agribusiness system, agriculture and its expansion in this territory involve a diverse array of land users. Here we (i) identified and mapped the most conspicuous groups of land users based on existing scientific literature and techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 52 publications
2
30
0
3
Order By: Relevance
“…This agricultural occupation includes multiple activities and high dynamics in smaller territorial extensions, which affects detection quality using MODIS data [24]. Another constraint is to differentiate the savanna types because they consist of a nearly continuous grass layer overlaid by a discontinuous tree layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agricultural occupation includes multiple activities and high dynamics in smaller territorial extensions, which affects detection quality using MODIS data [24]. Another constraint is to differentiate the savanna types because they consist of a nearly continuous grass layer overlaid by a discontinuous tree layer.…”
Section: Discussionmentioning
confidence: 99%
“…Hüttich et al [23] distinguish savanna types in South Africa from the in situ botanical survey combined with Landsat and MODIS images. Baldi et al [24] quantify the connections among landscape patterns, ecosystem functioning, and agricultural use in the Dry Chaco and Chiquitania ecoregions that cover parts of Argentina, Bolivia, and Paraguay using MODIS-Normalized Difference Vegetation Index (NDVI) time-series data. Portillo-Quintero et al [25] study the correlation between MODIS active fires and forest cover change in the tropical dry forest.…”
Section: Introductionmentioning
confidence: 99%
“…During low-rainfall periods land was allocated to livestock production, while crops were planted when precipitations increased (Viglizzo et al, 1997;Wolfe, 2011). As previous research in Argentina (Viglizzo and Roberto, 1989;Hutchinson et al, 1992;Riera and Pereira, 2009;Baldi et al, 2014) and US (Walthall et al, 2012) has demonstrated, an on-farm diversification of activities was a successful strategy to face climate variability in semiarid and sub-humid regions.…”
Section: Introductionmentioning
confidence: 88%
“…2013;Gasparri, Grau, and Sacchi 2015;Vallejos et al 2015;Volante and Paruelo 2015). Even highly remote forests like the Chiquitania in eastern Bolivia have declined by some 18 percent (Pinto-Ledezma and Mamani 2014; Baldi et al 2015).…”
Section: Monoculture Modernization and Malthusmentioning
confidence: 99%